V—XVII դդ. հայ-իսպանական պատմամշակութային կապերի պատմությունից - Ա. Գ. Արամյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Испания и испанцы были известны армянам с древнейших времен: они упоминаются в «Истории Армении» М. Хоренаци (V в.), в «Географии» А. Ширакаци (VII в.).Особенно крепнут армяно-испанские экономические, религиозные и культурные связи в период существования Киликийского армянского царства. Тесно переплетена с Испанией судьба последнего царя Киликийской Армении Левона VI Лузиняна. Spain and Spaniards were well known to Armenians from ancient times: they are mentioned in "The history of Armenia" by M. Khorenatsi (Vc.), in "Geography" by A. Shirakatsi (VIIc.). Armenian-Spanish economic, religious and cultural connections were especially stronger in the period of the existence of Cilician Armenian Kingdom. The destiny of the last king of Cilician Armenia Levon the VI Lusinian was tightly interlaced with Spain.
Keywords: History; Geography; Anthropology; Recreation; D History; GCC Culture and Cultural Processes